Professional Psychological Competence Its Factors and Types - H.Kh. Rajabova (Genius Journals, 2022)
This article investigates the basic information on the study of psychological competence, its individual types, description and systematization of its components, the stages of formation of professional skills, communicative and socio-cognitive competence.
Keywords: psychological and pedagogical competence; communicative competence; socio-cognitive verbal competence